2007
DOI: 10.1097/mpa.0b013e318040b332
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis

Abstract: In this high-risk population of heavy drinkers, the prevalence of pancreatitis is at least 3%. Our study provides preliminary data regarding potential cofactors for pancreatitis in heavy drinkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…The summary RRs of the five studies for ever ( versus never) smokers was 1.73 (95% CI: 1.18, 2.54), and the heterogeneity was not significant (Q = 6.58, P = 0.16, I 2 = 39.2%). The pooling of four studies [6,14,16,26] that evaluated current ( versus never) smokers also revealed a correlation between current smoking and pancreatitis (RR = 1.67, 95% CI: 1.03, 2.68). There was no significant heterogeneity among studies (Q = 5.66, P = 0.129, I 2 = 47.0%).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The summary RRs of the five studies for ever ( versus never) smokers was 1.73 (95% CI: 1.18, 2.54), and the heterogeneity was not significant (Q = 6.58, P = 0.16, I 2 = 39.2%). The pooling of four studies [6,14,16,26] that evaluated current ( versus never) smokers also revealed a correlation between current smoking and pancreatitis (RR = 1.67, 95% CI: 1.03, 2.68). There was no significant heterogeneity among studies (Q = 5.66, P = 0.129, I 2 = 47.0%).…”
Section: Resultsmentioning
confidence: 89%
“…Five studies, which included 660 patients, investigated the correlation between smoking and the development of pancreatitis (Fig 4) [6,7,14,16,26]. Study data were collected from 1982 to 2014.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data in Table 1 show that smoking tends to be higher in methadone maintenance samples compared with outpatient. The 2007 sample (Yadav, Eigenbrodt, Briggs, Williams, & Wiseman, 2007) involves veterans seeking outpatient detoxification, and smoking in this sample (87.2%) may be atypical when compared with other outpatient samples in the data.…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated incident hospitalizations rather than incident diagnosis of CP in unique patients, so we may have missed patients who were not hospitalized or did not have symptoms. There are limited data on the validation of CP diagnosis codes [28,29]. Because we could not validate diagnostic codes, we may have overestimated true CP cases, which to some extent would offset the underestimation of cases managed as outpatients or who are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%